Exploring the roles of phytobiotics in relieving the impacts of Edwardsiella tarda infection on fish: a mini-review - Goh, Khang Wen; Abdul Kari, Zulhisyam; Wee, Wendy; Zakaria, Nik Nur Azwanida; Rahman, Mohammad Mijanur; Kabir, Muhammad Anamul; Abdul Hamid, Noor Khalidah; Tahiluddin, Albaris B.; Kamarudin, Ahmad Syazni; Téllez–Isaías, Guillermo; Wei, Lee Seong (Frontiers in Veterinary Science, 2023)
Edwardsiellosis caused by Edwardsiella tarda resulted in significant economic losses in aquaculture operations worldwide. This disease could infect a wide range of hosts, including freshwater, brackish water, and marine aquatic animals. Currently, antibiotics and vaccines are being used as prophylactic agents to overcome Edwardsiellosis in aquaculture. However, application of antibiotics has led to antibiotic resistance among pathogenic bacteria, and the antibiotic residues pose a threat to public health. Meanwhile, the use of vaccines to combat Edwardsiellosis requires intensive labor work and high costs. Thus, phytobiotics were attempted to be used as antimicrobial agents to minimize the impact of Edwardsiellosis in aquaculture. These phytobiotics may also provide farmers with new options to manage aquaculture species' health. The impact of Edwardsiellosis in aquaculture worldwide was elaborated on and highlighted in this review paper, as well as the recent application of phytobiotics in aquaculture and the status of vaccines to combat Edwardsiellosis. This review also focuses on the potential of phytobiotics in improving aquatic animal growth performance, enhancing immune system function, and stimulating disease resistance.